Discovering price-load relationships in California's electricity market. - Vucetic, S.
This paper reports on characterizing price behavior in the California electricity market. Market participants, that is, producers, consumers and traders, are highly motivated by the potential for profits to develop strategies to explore, and exploit, the limits of system operation. These strategies should be reflected in the market as different price to load relationships. We show that a number of regimes, i.e., characteristic behaviors, exist in the price time series, and provide a brief analysis of each regime. Knowledge of the number of regimes, their characteristics and switching dynamics allows insight into the market and power system performance
Keywords: California electricity market; Deregulation; Power consumers; Power producers; Power system performance; Power traders; Price prediction; Price time series; Price-load relationships; Switching dynamics; System operation limits